PEMBERDAYAAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) LOKAL MELALUI PEMASARAN DIGITAL DI DESA BATU MEKAR,, KABUPATEN LOMBOK BARAT - Rakmah, Aira; Sigalingging, Cinthya Natasya; Ramadani, Nafisah Kurniawati; Mulyana, Sulastri; Irawan, Yudi; Ilmi, Baiq Iva Nur Jannatul; Fanduwinata, Fina; Pratama, Lalu Bobi; Haryani, Baiq Aristawidya; Nuraini; Buhari, Nurliah (Jurnal Wicara, 2025)
MSMEs play a vital role in the Indonesian economy, particularly in creating jobs and driving the economy. However, MSMEs in rural areas still face limited market access and technology, particularly in utilizing digital marketing. This situation is also experienced by MSMEs in Batu Mekar Village, most of whom operate in the snack food sector but lack an effective understanding of digital marketing strategies. Recognizing this issue, the University of Mataram Community Service Program (KKN-PMD) provided mentoring to MSMEs in Batu Mekar Village, focusing on local product processing, branding enhancement, and digital marketing outreach. The methods used included field observation, interviews, direct mentoring, business legalization, and digital marketing education. The results of the activities showed that the assisted MSMEs achieved improved product quality through improved packaging, simple financial management training, and the use of social media for promotion. Furthermore, several MSMEs successfully obtained business legality in the form of NIB (National Business License) and SPP-IRT (Special Business License), which strengthened their product competitiveness. Thus, this KKN program makes a real contribution to empowering MSMEs in Batu Mekar Village through improved branding, business management, and digital marketing utilization, thus making MSMEs better prepared to compete in a wider market.